Meningkatkan Kesadaran Pentingnya Pendidikan dan Kesehatan pada Anak-Anak Suku Kokoda - Nika Fetria Trisnawati; Muhamad Faizal Arianto; Arie Anang Setyo (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This service aims to increase the awareness of the children of the Kokoda Tribe in Warmon Village about the importance of formal education and health. The methods used are counseling and demonstrations. Counseling was carried out to provide awareness and motivation to the children of the Kokoda tribe, while demonstrations were conducted to provide examples and direct practice on how to wash hands and brush their teeth properly and correctly. In addition to counseling and demonstrations, in this service activity, gifts in the form of stationery and personal hygiene kits were also distributed to the children of the Kokoda Tribe, Warmon Village. After the dedication, it was seen that the children of the Kokoda Tribe in Warmon Village became motivated and enthusiastic and were diligent in going to school.